Penyuluhan dan Analisis Pengetahuan Wanita Terkait Infeksi Staphylococcus aureus di Desa Babelan Kota Kabupaten Bekasi: The Health Education and Knowledge Analysis Against Staphylococcus aureus Infection of Women at Desa Babelan Kota, Bekasi District - Zahara, Indah; Ekayanti, Meiliza; Amalia, Putri; Umamah, Siti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Staphylococcus aureus is a pathogen that causes various clinical manifestations; it couldn't cause skin infections in healthy people, but if it enters the bloodstream or internal tissues, it might cause serious infections. Desa Babelan Kota, Bekasi District, is a densely populated location with secondary education backgrounds. The aim of this study is to increase awareness and would impact the quality of life. The method was health education, analysis of the characteristics, and knowledge before and after education. The characteristic results of participant (n) 25 females are 17-25 years (44%) with the majority's highest education in Junior High School (52%) and High School, 19.2%. The average knowledge based on the pretest results is 74.1% (adequate), and the posttest is 85.2% (good). The Non-Parametric analysis of 2 paired samples and the Wilcoxon test obtained a significance value of 0.550 (p >0.05). It concluded that there was no significant difference in the average knowledge of respondents before and after health education.